Black Gold: A Black Feminist Art History of 1920s Montréal - Joachim, Joana (Canadian Journal of History, 2021)
The 1920s have been touted as the golden era of jazz and Black history in Montréal. Similarly, the decade is well known for the Harlem Renaissance, a key moment in African American art history. Yet this period in Black Canadian art histories remains largely unknown. As a first step toward shedding some light on this period in Black Canadian art history, I propose to use what I term a Black feminist art-historical (bfah) praxis to discuss some visual art practices undoubtedly active alongside well-known jazz musicians and cultural producers in 1920s Montréal. This paper presents an overview of critical race art history and feminist art history, as well as Black feminist approaches to visual representation, to outline what might be considered four tenets of bfah praxis. Applying these tenets, I propose that a new art history may emerge from well-known art objects and practices as well as lesser-known ones. I posit that through a deliberately bfah approach, new meanings emerge and the voices of Black women, even when obstructed by mainstream white narratives, may begin to stand out and shed light upon a variety of histories. This praxis aims to underline the subtext lurking at the edges of these images and to make intangible presences visible in the archive and in art history. I propose bfah as a strategy for more nuanced discussion of the work of Black Canadian artists and histories that have by and large been left out of official records.

Black Minstrelsy on Canadian Stages: Nostalgia for Plantation Slavery in the Nineteenth and Twentieth Centuries - Thompson, Cheryl (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Le blackface minstrelsy, qui a vu le jour dans le nord-est des États-Unis dans les années 1820 et 1830, mettait en scène des artistes blancs, principalement des hommes, qui franchissaient les frontières raciales en imitant des Afro-Américains avec la musique, l’humour et la danse prétendument « authentiques », courants dans les plantations du sud. Dans les années 1860, les Afro-Américains nouvellement émancipés se produisaient également sur scène en blackface. À la fin du XIXe siècle, cependant, les acteurs noirs ne se grimaient plus en noir, mais ils devaient toujours perpétuer les stéréotypes de la plantation. Ces troupes étaient dirigées par des directeurs noirs et blancs qui présentaient leurs spectacles comme « authentiques » et « nostalgiques ». Ces éléments du spectacle de minstrel noir — surtout ses représentations soi-disant « réelles » du Sud des États-Unis et de l’esclavage dans les plantations — ont trouvé un écho auprès du public canadien. Ils constituent donc une autre perspective d’approche — en dehors des politiques d’immigration et Jim Crow de facto — pour expliquer la présence du racisme et de la xénophobie anti-Noirs au Canada à la fin du XIXe siècle et au début du XXe siècle. En examinant le contenu de la minstrelsy noire, le rôle joué par les directeurs dans ses productions et la promotion dans les journaux, cet article soulève des questions sur l’étendue à laquelle les Canadiens ont été historiquement complices du dénigrement des Noirs.